Assessment by three‐dimensional power Doppler ultrasound of cerebral blood flow perfusion in fetuses with congenital heart disease. (June 2015) - Zeng, S.; Zhou, J.; Peng, Q.; Tian, L.; Xu, G.; Zhao, Y.; Wang, T.; Zhou, Q.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2015; 45: 629–629